Responsible Innovation in Business - Jarmai, Katharina; Tharani, Adele; Nwafor, Caroline (Responsible Innovation : Business Opportunities and Strategies for Implementation, 2020)
This chapter introduces responsible innovation in a business context. The first part explains the basic terms that constitute responsible innovation from a business perspective. The second part presents tangible business practices that operationalise responsible innovation and introduces two good practice examples that hint at the variety of ways in which responsible innovation can be implemented in companies.
Keywords: Innovation responsable; Responsible research and innovation

Limits to responsible innovation - de Hoop, Evelien; Pols, Auke; Romijn, Henny (Journal of Responsible Innovation, 2016)
Responsible Innovation (RI) is a young field of research that has nevertheless had remarkable successes in dissemination within academic and political circles. However, there is relatively little awareness of its limits, blind spots and situations in which it cannot be used for actual innovation trajectories. Without such awareness, there is a risk that RI may get hollowed out and turned into a tool for ‘greenwashing’. To examine RI’s limits, we present a case study on biofuel innovation in Hassan, South India. This case study demonstrates that there are important barriers that may make it difficult to conduct innovation according to RI values. In particular, we highlight the following factors that emerge from our case study and need more attention in order to be included and adequately theorised in the RI literature: material barriers to innovation, engagement with abandoning or reducing existing practices as a consequence of innovation, power differences and dependencies, (un)clear demarcation of responsibilities, strategic behaviour and, lastly, different, diverging and even contradictory interests. We demonstrate that such factors may obstruct the possibility to innovate in a responsible way, leading us to our core observation that RI should be about innovating responsibly – or not innovating at all.
Keywords: Innovation responsable

Developing a framework for responsible innovation - Stilgoe, Jack; Owen, Richard; Macnaghten, Phil (Research Policy, 2013)
The governance of emerging science and innovation is a major challenge for contemporary democracies. In this paper we present a framework for understanding and supporting efforts aimed at ‘responsible innovation’. The framework was developed in part through work with one of the first major research projects in the controversial area of geoengineering, funded by the UK Research Councils. We describe this case study, and how this became a location to articulate and explore four integrated dimensions of responsible innovation: anticipation, reflexivity, inclusion and responsiveness. Although the framework for responsible innovation was designed for use by the UK Research Councils and the scientific communities they support, we argue that it has more general application and relevance.
Keywords: Gouvernance; Innovation responsable; Nouvelles technologies; Éthique

Guide de l'utilisateur - Outil d’évaluation de l'Innovation responsable en santé (IRS) - In Fieri (Notion)
A new tool that blends your everyday work apps into one. It's the all-in-one workspace for you and your team
Keywords: Innovation responsable; Libre accès; Outils; Publication UdeM; Santé